Swear Words Analysis in the Indonesia Version of the Miracle in Cell No. 7 Film - Muhid, Abdul; Suktiningsih, Wiya; Kawara, Morinawa (CV. Strata Persada Academia, 2023)
This research scrutinizes the types of swearing words in “Miracle in Cell No.7” Indonesian Movie. The researchers revisit the types of swear words theory from Andersson & Trudgill. It aims to reveal the types of swear words found in the film Miracle in Cell no.7 based on the theory applied. The research method used is interpretive qualitative with a sociolinguistic approach because the data used is in linguistic phenomena contained in the film. The main data which is most used is the phrases and swear words uttered by the main character in the film Miracle in Cell no. 7 Indonesia Movie. The data is collected using the Listening (watching) technique and recording (notetaking) the swear words in the film. The collected data is then analysed based on the theory adapted from Andersson & Trudgill. From the results of data analysis, there were found 3 (three) types of swear words. Among the four types of swear words; Abusive types, Expletive types and Humor types.